Molecular pharmacology of VEGF-A isoforms: binding and signalling at VEGFR2 - Peach, Chloe; Mignone, Viviane; Arruda, Maria; Alcobia, Diana; Hill, Stephen; Kilpatrick, Laura; Woolard, Jeanette (MDPI, 2018)
Vascular endothelial growth factor-A (VEGF-A) is a key mediator of angiogenesis, signalling via the class IV tyrosine kinase receptor family of VEGF Receptors (VEGFRs). Although VEGF-A ligands bind to both VEGFR1 and VEGFR2, they primarily signal via VEGFR2 leading to endothelial cell proliferation, survival, migration and vascular permeability. Distinct VEGF-A isoforms result from alternative splicing of the Vegfa gene at exon 8, resulting in VEGFxxxa or VEGFxxxb isoforms. Alternative splicing events at exons 5–7, in addition to recently identified posttranslational read-through events, produce VEGF-A isoforms that differ in their bioavailability and interaction with the co-receptor Neuropilin-1. This review explores the molecular pharmacology of VEGF-A isoforms at VEGFR2 in respect to ligand binding and downstream signalling. To understand how VEGF-A isoforms have distinct signalling despite similar affinities for VEGFR2, this review re-evaluates the typical classification of these isoforms relative to the prototypical, “pro-angiogenic” VEGF165a. We also examine the molecular mechanisms underpinning the regulation of VEGF-A isoform signalling and the importance of interactions with other membrane and extracellular matrix proteins. As approved therapeutics targeting the VEGF-A/VEGFR signalling axis largely lack long-term efficacy, understanding these isoform-specific mechanisms could aid future drug discovery efforts targeting VEGF receptor pharmacology. View Full-Text